Stage 3 HIV Patient with Severe Dysfunctional APGAR Score: A Palliative Approach - Prastiwi, Silvia Hari; Wasityastuti, Widya (Faculty of Medicine, Public Health, and Nursing, 2025)
Mr. D, a 45 years old patient was visited at home for his HIV stage 3. The patient admitted that he had shortness of breath that was not affected by activity and there was no swelling in both legs. He also has a cough that produces sticky phlegm. He experiences diarrhea, even though it doesn’t happen every day. He was diagnosed with HIV since 2012 and admitted that did not comply with taking ARTs. He underwent the test two years after his wife was diagnosed with HIV; during this time, he also had persistent shortness of breath and lost weight due to a co-infection with tuberculosis. He acknowledged not taking ARTs on a regular basis for about ten years after receiving his diagnosis because he believed he had accepted his predicament. Since four years ago, his wife has been gone, leaving him with their children.He has two sons: the oldest, a 20-year-old who provides the family's foundation, and the younger, a 17-year-old who is still in school. The patient and their kids currently don't get along well because there isn't much communication between them and because the kids spend much of their time alone at home and don't say hello to each other. Because of the low economic status and the family's lack of concern for the patient's diet, the patient consumes the same foods every day, such as instant noodles or fried eggs.The patient's shortness of breath prevents him from working and interferes with his daily routines. He stated that because he was alone at home and was experiencing discomfort with his shortness of breath, he could only rest and lie down there. The patient was urged to be referred to Sardjito Hospital by the doctor at the Community Health Center (Puskesmas), but he was rejected on the grounds that he could not have a companion with him.